Peculiarities of Pedagogical Internship Organization for Future Specialists of Foreign Philology in Blended Learning - Oksana Rezvan; Alla Krokhmal (Educational Challenges)
The competitiveness of the professional training of future philologists depends on the opportunities for professional realization, due to the formation of specific competencies, one of which is the competency of teaching activities. The specified factor encourages the creation of students’ conditions to obtain opportunities for professional realization in the practical activity of a teacher in secondary education.